Computed tomography for head injuries in children: Change in Australian usage rates over time. (April 2017) - Oakley, Ed; May, Rachel; Hoeppner, Tobias; Sinn, Kam; Furyk, Jeremy; Craig, Simon; Rosengarten, Pamela; Kochar, Amit; Krieser, David; Dalton, Sarah; Dalziel, Stuart; Neutze, Jocelyn; et al.
Abstract: Objective: Paediatric head injury is a common presentation to the ED. North American studies demonstrate increasing use of computed tomography (CT) brain scan (CTB) to investigate head injury. No such data exists for Australian EDs. The aim of this study was to describe CTB use in head injury over time in eight Australian EDs. Methods: Retrospective ED electronic database and medical imaging database audit was undertaken for the years 2001–2010 by International Classification of Diseases (ICD) 9 or 10 code for head injury in children <16 years. EDs and medical imaging departments of eight hospitals in Australia (five tertiary referral and three mixed departments). Data for ED presentations with head injury, and all CTB performed by medical imaging were merged to obtain a data set of CTB performed within 24 h for head injury‐related attendances to the ED. Descriptive and comparative analysis of CTB rates was performed. Results: The rate of CTB over the decade was 10.2% (95% confidence interval (CI) 9.9–10.5). The annual rate varied from 9.5% (95% CI 8.2–10.9) to 12.5% (95% CI 11.2–13.9). CTB use did not increase over time. Median year of age at time of CT scan was 4 years, with an interquartile range of 1.5–9.4 years. Overall there was a 9.2% increase in the CTB scan rate for every additional year of age at presentation (95% CI 6.6–12.1; P < 0.001). Conclusion: CTB use in head injuries did not increase during the study period, and rates of CTB were less than reported for North America.